ANALISA ASSESMEN STANDAR PELAYANAN KESEHATAN DI INSTALASI GAWAT DARURAT RS PKU MUHAMMADIYAH SRUWENG TAHUN 2012 - Noffi Julia Sandy; Aris Suparman Wijaya; Irma Risdiana (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
Government regulations governing the technical requirements contained in the emergency room in RI KEPMENKES NO. 856/Menkes/SK/IX/2009 Standards governing the ER (emergency room) .This study aims to find out analysis of assessment results PKU Muhammadiyah Hospital emergency room services Sruweng and compliance with the standards according to KEPMENKES RI NUMBER 856/Menkes/SK/IX/2009 Standards governing the ER Hospital. The study is qualitative research case study design. Research subjects were all medical and paramedical personnel who served in the emergency room, facilities and existing facilities and services in the IGD. Method of data collection is done by using the instruments of observation checklist with a list of statements of service standards according to IGD Kepmenkes No. 856/Menkes/SK/IX/2009, further in-depth interviews. The results the assessment conducted in PKU Muhammadiyah Hospital ER Sruweng through field observations and interviews were IGD service has exceeded the standard level of I is by achieving 103.50% and the achievement of outcomes assessment for level II emergency room services is quite high is 88.81%. Conclusion is more than the standard level I. However, to reach higher level is level II, IGD PKU Muhammadiyah Hospital Sruweng still require improvement and development to meet the service standards.